Effect of Amino Acids on the Synthesis of NiFe2O4/Au Hybrid Nanoparticles - Diana Nemkova; Svetlana Saikova; Anton Krolikov (Crystals)
Hybrid nanoparticles, composed of magnetic oxides and gold, have garnered significant interest due to their potential applications in various fields, including catalysis, diagnostics, and nanomedicine. In this study, the effect of reaction parameters on the reduction of HAuCl4 by different non-sulfur amino acids (glycine, L-serine, L-tryptophan, and L-tyrosine) was determined using the design of experiment (DOE) method. The results of the analysis of the regression equations were used to select the conditions and develop a methodology for the preparation of the hybrid magnetic NiFe2O4/Au nanoparticles (NPs) by direct reduction of gold on the magnetic surface using the aforementioned amino acids as the reducing and stabilizing agents simultaneously. The materials were characterized using XRD, TEM, XPS, and Vis/FTIR spectroscopy. The results indicate the successful synthesis of magnetic NiFe2O4/Au nanoparticles with all amino acids used, but the size of the gold crystals, their surface density, and the details of the NP structure (inlaid or a core–shell structure) depend on the amino acid used. The mechanism of the gold deposition on the magnetic core surface and the difference in the effect of various amino acids are discussed. The developed synthesis strategy can be extended to other metal ferrites and iron oxides.